In-situ tuning of Sn doped In2O3 (ITO) films properties by controlling deposition Argon/Oxygen flow - Najwa, S.; Shuhaimi, Ahmad; Talik, Noor Azrina; Ameera, N.; Sobri, M.; Rusop, Mohamad (Elsevier, 2019)
In this work, we report that the properties of Sn-doped In 2 O 3 (ITO) can be properly tuned by varying Argon/ Oxygen (Ar/O 2 ) percentage during the sputtering process from 7% O 2 to 93% O 2 . The characteristics of the ITO grown in oxygen deficient to the oxygen-rich condition are properly studied. It is found that there is a strong correlation between the concentration incorporation of oxygen with the properties of ITO films. ITO films were grown in oxygen deficient condition (7% O 2 ) resulted in a rougher surface, wider band gap, and lower resistivity compared to the other films grown with 33%, 67%, and 93%. Blue shifts in absorbance edge and band gap widening indicate that the number of carrier concentration was also changed linearly with the presence of oxygen in the film. These findings provide a simple way to effectively tune the properties of ITO films for ITO to be applied in optoelectronics, power device as well as sensor applications. © 2019 Elsevier B.V.